ByzRev 05.2023.028: Roald Dijkstra – Paul van der Velde (eds), Humour in the Beginning.: Religion, Humour and Laughter in Formative Stages of Christianity, Islam, Buddhism and Judaism (Topics in humor research 10). Amsterdam – Philadelphia: John Benjamins Publishing Company 2022. - Marciniak, Przemysław (The Byzantine Review, 2023)
Roald Dijkstra – Paul van der Velde (eds), Humour in the Beginning. Religion, Humour and Laughter in Formative Stages of Christianity, Islam, Buddhism and Judaism (Topics in humor research 10). Amsterdam – Philadelphia: John Benjamins Publishing Company 2022. XII, 306 pp. – ISBN 978-90-272-5746-8